2020
DOI: 10.3390/ani10020320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Farrowing Environments on the Behavior of Sows and Piglets

Abstract: We investigated the effect of different farrowing systems on the behavior of sows and piglets. In total, 22 hybrid sows (Yorkshire × Landrace) were randomly assigned into three farrowing systems, farrowing crate (FC), free farrowing pen with sloping walls (FFS), and free farrowing pen with sloping walls and nest materials (FFSN). The FFS and FFSN sows were more active, and exhibited less abnormal behaviors compared with the FC sows before and after parturition. FFS and FFSN piglets were more active compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…Similar to our results, Chidgey et al [ 11 ], comparing temporary crates (opening at day 4) with conventional farrowing crates, found that after opening the crate, a greater proportion of piglets died by being laid on. In contrast to our findings, other studies, such as [ 16 , 18 , 19 , 24 ] did not find a significant effect of housing on piglet mortality from being laid on.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, Chidgey et al [ 11 ], comparing temporary crates (opening at day 4) with conventional farrowing crates, found that after opening the crate, a greater proportion of piglets died by being laid on. In contrast to our findings, other studies, such as [ 16 , 18 , 19 , 24 ] did not find a significant effect of housing on piglet mortality from being laid on.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the total percentage of piglet mortality was higher for T4 litters than T7 and PC, and T7 did not differ from the PC group. This is consistent with studies that have found no differences in piglet survival when comparing loose housed sows with crated sows [ 5 , 17 , 18 , 19 ]. In contrast, a meta-analysis by Glencorse et al [ 20 ], found that the risk of total piglet mortality was 14% higher for animals raised in pens compared with those in crates.…”
Section: Discussionsupporting
confidence: 92%
“…Recent work showed that environmental enriched housing could have positive effects on the development of the immune system and the establishment of gut microbiota in early life [ 133 ]. Enabling sows to build a nest and offering straw during farrowing and lactation can prevent skin and claw lesions in piglets [ 134 ], increase activity, and reduce abnormal behaviour in the sows [ 135 ]. Furthermore, there is a knock-on effect of reducing sows’ stress at the end of gestation in that it may positively affect the offspring, influencing the activity of the HPA axis and reducing the incidence of aggressiveness and belly-nosing [ 136 ].…”
Section: Improving Housing Environment and Management Practices To Re...mentioning
confidence: 99%
“…In this regard, the amount of nesting material and free space available at parturition may be important for the sow’s motivation to perform nesting behavior. Loose-housed sows are more active and exhibit less abnormal behaviors than sows in farrowing crates [ 27 ]. In the same study, nesting materials improved sow and piglet investigative behavior.…”
Section: Discussionmentioning
confidence: 99%